Employee’s Performance at PT. Mitra Tri Sakti - Saraswati, Ni Putu Ayu Sintya; Widyani, Anak Agung Dwi; Sagita, Luh Putu Diah Inten (AIBPM Publisher, 2020)
This study aims to determine the effect of organizational culture on employee’s performance to work motivation as an intervening variable on PT. Mitra Tri Sakti. The population is all of PT. Mitra Tri Sakti employees. The samples are 50 regular employees. Data analysis technique uses alternative methods of Structural Equation Model Partial Least Square obtained by Smart PLS. The results show that organizational culture has a positive and significant effect on employee’s performance, and work motivation. Work motivation, and organizational culture have a positive and significant effect on employee’s performance through work motivation as an intervening.